2009
DOI: 10.1074/jbc.m806927200
|View full text |Cite
|
Sign up to set email alerts
|

Versican/PG-M Assembles Hyaluronan into Extracellular Matrix and Inhibits CD44-mediated Signaling toward Premature Senescence in Embryonic Fibroblasts

Abstract: Versican/PG-M is a large chondroitin sulfate proteoglycan of the extracellular matrix which interacts with hyaluronan at the N-terminal G1 domain, composed of A, B, and B subdomains. Recently, we generated knock-in mice Cspg2 ⌬3/⌬3 , whose versican, without the A subdomain, has decreased hyaluronan (HA) binding affinity, thereby exhibiting reduced deposition of versican in the extracellular matrix. Here, we show that the Cspg2 ⌬3/⌬3 fibroblasts within 20 passages proliferate more slowly and acquire senescence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 37 publications
(16 reference statements)
2
40
0
Order By: Relevance
“…As HA is known to regulate proliferation in a great number of cells (23), it was not surprising to find that inhibition of HA synthesis alters cell cycle genes. On the other hand, the link between HA and p53 is not known, although recently, it was reported that reduction of an HA/versican ECM induced senescence and p53 accumulation in fibroblasts (24).…”
Section: Resultsmentioning
confidence: 99%
“…As HA is known to regulate proliferation in a great number of cells (23), it was not surprising to find that inhibition of HA synthesis alters cell cycle genes. On the other hand, the link between HA and p53 is not known, although recently, it was reported that reduction of an HA/versican ECM induced senescence and p53 accumulation in fibroblasts (24).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of hyaluronan, it may be degraded by hyaluronidase because Crtl1 could retard the degradation of hyaluronan in proteoglycan aggregates in vitro (Rodriguez and Roughley, 2006). Alternatively, the degradation may be secondary to the lack of the nodal lecticans, including versican, in Bral1-deficient mice, because versican may function to maintain hyluronan levels in the ECM (Suwan et al, 2009).…”
Section: Bral1 Is Indispensable For the Stable Localization Of Extranmentioning
confidence: 99%
“…fibroblasts with lower Vcan expression exhibit decreased levels of proliferation 13 and collagen synthesis (unpublished data). Thus, the decrease in the stromal region could be due to reduced fibroblast growth and diminished collagen biosynthesis caused by loss of Vcan expression.…”
Section: ᭝3/᭝3mentioning
confidence: 99%
“…Cells were incubated in 0.5 ml of 1.5 M Tris-HCl, pH 7.3, 0.15 M NaCl, 10 mM CaCl 2 and 10 U of protease K for 2 hr at 558C. 13 After centrifugation at 14,000g at 48C for 25 min, the supernatant was applied to a sandwich enzyme-linked immunosorbent assay (Echelon Biosciences, Salt Lake City, UT) according to the manufacturer's instructions.…”
Section: Quantification Of Hamentioning
confidence: 99%
See 1 more Smart Citation